Stewardship Manual: A guide to regulatory management for meaningful impact - Kulkarni, Gururaj Guddappa (International Rice Research Institute, 2024)
The International Rice Research Institute (IRRI) plays a pivotal role in addressing global food security by advancing rice science and innovation. Stewardship at IRRI is a critical framework that ensures sustainable and ethical management of the institute’s resources, research outputs and partnerships.